2006
DOI: 10.1111/j.1365-2125.2006.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of St John’s wort extracts on CYP3A: a systematic review of prospective clinical trials

Abstract: AimThe aim of this systematic review was to assess the quality and outcomes of clinical trials investigating the effect of St John's wort extracts on the metabolism of drugs by CYP3A. MethodsProspective clinical trials assessing the effect of St John's wor t (SJW) extracts on metabolism by CYP3A were identified through computer-based searches (from their inception to May 2005) of Medline, Cinahl, PsycINFO, AMED, Current Contents and Embase, hand-searches of bibliographies of relevant papers and consultation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 65 publications
2
87
0
1
Order By: Relevance
“…Recently, interactions of SJW with prescription drugs have been reported. SJW, at the dose recommended for the treatment of mild to moderate depression, is a potent inducer of cytochrome P450 enzymes resulting in decrease plasma concentration of a number of drugs used in co-medication (Whitten et al 2006). Recent studies show that the degree of enzyme induction by SJW correlates strongly with the amount of hyperforin found in the product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, interactions of SJW with prescription drugs have been reported. SJW, at the dose recommended for the treatment of mild to moderate depression, is a potent inducer of cytochrome P450 enzymes resulting in decrease plasma concentration of a number of drugs used in co-medication (Whitten et al 2006). Recent studies show that the degree of enzyme induction by SJW correlates strongly with the amount of hyperforin found in the product.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the degree of enzyme induction by SJW correlates strongly with the amount of hyperforin found in the product. High-dose hyperforin extracts (>10 mgday −1 ) had outcomes consistent with CYP3A induction whereas low-dose hyperforin extracts (<4 mgday −1 ) demonstrated no significant effect on CYP3A (Whitten et al 2006;Madabushi et al 2006). We observed that SJW reduced NO induced nociceptive behavior at very low doses containing an amount of hyperforin (0.21 mg) unable to produce clinical significant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant drug interactions of Hypericum extracts have been reported in several case reports and drug interaction studies and have been systematically reviewed [12,13]. The underlying mechanism is an induction of mainly intestinal CYP3A and p-glycoprotein [14] leading to decreased plasma concentration and potential therapeutic failure of substrates of CYP3A and p-glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Whitten et al [12] and Madabushi et al [6], most clinical studies investigating drug interactions by St. John's wort in general and specifically CYP3A induction used St. John's wort extracts with high hyperforin content. While the studies using hyperforin-rich St. John's wort extracts consistently reported clinically relevant interaction consistent with CYP3A induction, only a few studies with extracts with low hyperforin content have been performed [6,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation